Antiparallel Four-Stranded Coiled Coil Specified by a 3-3-1 Hydrophobic Heptad Repeat - Deng, Yiqun (Structure, 2006)
Coiled-coil sequences in proteins commonly share a seven-amino acid repeat with nonpolar side chains at the first (a) and fourth (d) positions. We investigate here the role of a 3-3-1 hydrophobic repeat containing nonpolar amino acids at the a, d, and g positions in determining the structures of coiled coils using mutants of the GCN4 leucine zipper dimerization domain. When three charged residues at the g positions in the parental sequence are replaced by nonpolar alanine or valine side chains, stable four-helix structures result. The X-ray crystal structures of the tetramers reveal antiparallel, four-stranded coiled coils in which the a, d, and g side chains interlock in a combination of knobs-into-knobs and knobs-into-holes packing. Interfacial interactions in a coiled coil can therefore be prescribed by hydrophobic-polar patterns beyond the canonical 3-4 heptad repeat. The results suggest that the conserved, charged residues at the g positions in the GCN4 leucine zipper can impart a negative design element to disfavor thermodynamically more stable, antiparallel tetramers.